The Influence of Multimodal Visual Methodologies on EFL University Students’ Audio-Visual Comprehension, Verbal and Nonverbal Communication - Ibrahim Hassan Ali Al-jumaily; Istabraq Tariq Jawaad Alazzawi (Journal of Language and Education, 2025)
Background: Technological devices and multimedia resources are enhancing verbal communication in language learning. Vodcasts, combining audiovisual material with visuals, help develop mental schemas. Nonverbal communication is challenging for students, potentially impacting grades. Verbal communication analysis examines speech structure, social uses, roles, and power relations, highlighting the complexity of verbal communication in everyday interactions.